Technology-Facilitated Domestic Violence and Coercive Control: A Normative Legal Study on Victim Protection in Digital Intimate Relations - Sutiawati (Punggawa Law Review, 2026)
Technology-facilitated domestic violence raises a doctrinal difficulty that cannot be solved by adding more cybercrime provisions to existing legal systems. The central problem lies in the way law classifies harm. Digital abuse in intimate relationships may appear as fragmented conduct: repeated messages, access to cloud storage, location tracking, control over banking applications, threats to circulate intimate images, or the misuse of smart-home devices. Assessed separately, each act may look minor, technically ambiguous, or difficult to prove. Within an abusive relationship, however, those acts may operate as coercive control. This article uses normative legal research to examine how domestic violence law should recognise technology-facilitated coercive control while avoiding an overbroad criminal category. The analysis relies on primary legal materials, including the Serious Crime Act 2015, the Domestic Abuse Act 2021, the Domestic Abuse (Scotland) Act 2018, the Online Safety Act 2023, the EU Digital Services Act, Australia’s Online Safety Act 2021, and selected coercive-control reforms in New South Wales. It also draws on recent journal literature concerning intimate partner violence, coercive control, image-based sexual abuse, digital evidence, and victim protection. The article argues that digital abuse should be legally treated as domestic violence where the conduct forms part of a pattern of domination, surveillance, intimidation, sexual coercion, economic restriction, or post-separation control. It further argues that digital evidence must be handled through a victim-centred protocol based on necessity, specificity, minimisation, and protected disclosure. A stronger legal model does not need to abandon due process. It needs to read digital facts in their relational setting.